Contents and Value of a Judicial Parting Word by Juror Chairman in Modern Russian Criminal Trial - Epikhin, Alexander; Zaytsev, Oleg; Mishin, Andrey; Mukhametshin, Timur (Journal of History Culture and Art Research, 2018)
Russian criminal proceedings undergo numerous changes aimed at criminal proceeding efficiency improvement. The differentiation of criminal justice includes the difference of criminal procedures. Some of them simplify, while others complicate the solution of guilt (innocence) issue. The consideration of a criminal case by a court with the participation of jurors is singled out among such complicated forms of criminal proceedings. The guilt or the innocence is determined by the jury in an advisory room after the study of the evidence brought by lawyers and prosecutors. Before the meeting of jurors takes place, the law establishes the procedure of a parting word announcement by a presiding judge (a professional judge leading the process). Such a judge announcement to a jury has special requirements set by Russian criminal law procedure, the violation of which may lead to the cancellation of the sentence. In addition, the article highlights the importance of ensuring the safety of all participants of the criminal process, including the jury. In the Russian criminalistics, the use of methods is associated traditionally with pre-trial proceedings on a criminal case. However, recently there has been some interest in forensic tactics development for a court session. In this paper, they showed the feature of trial forensic method use and the peculiarity of such development mastering.